TRENDS AND FACTORS THAT INFLUENCED THE INFANT MORTALITY RATE IN KLATEN DISTRICT IN 2009 – 2021 - Yuliana Ristantya Ningsih; Ulfah Sulistyowati; Merlin Swantamalo Magna (Proceedings of the 1st International Conference on Social Science (ICSS), 2022)
This study aims to determine (1) the trend of infant mortality rate (IMR) in Klaten Regency and (2) determine the socioeconomic factors that influence the IMR. The method used in this research is the descriptive quantitative method. The independent variables in this study are the Depth of Poverty Index, the Human Development Index (IPM), and the Net Participation Rate. The dependent variable in this study was the Infant Mortality Rate (IMR) which was then tested by multiple linear regression analysis. The results showed that during 2009-2021, there was an increase in the IMR in Klaten Regency at a rate of 0.4% per year. The Depth of Poverty Index, the Human Development Index (IPM), and the Net Participation Rate have a significant effect of 96.9% on the IMR, and other factors outside the study influence the remaining 6.1%.